Pengaruh Penerapan Corporate Social Responsibility, Profitabilitas, Karakteristik Eksekutif, Dan Koneksi Politik Terhadap Penghindaran Pajak(Studi Empiris pada Perusahaan BUMN Yang Terdaftar di BEI Tahun 2011-2015) - Lugesti, Fibria Rara, Zulfa Irawati, S.E., M.Si (2017)
The purpose of this study was to determine the effect of adoption of Corporate Social Responsibility, Profitability, Executive Characteristics, and Political Connections On Tax Avoidance in state-owned enterprises listed on the Stock Exchange in 2011-2015. The hypothesis in this study is Corporate Social Responsibility, Profitability, Political Connections negative and significantly effect on the Avoidance of Double Taxation and the Executive Characteristics positive and significantly effect on Tax Avoidance. The population of this research is state-owned enterprises listed on the Indonesia Stock Exchange in the year 2011 to 2015. The research method of sampling with purposive sampling method, with some predetermined criteria, the number of samples is as many as 16 companies. The research data is secondary data obtained from IDX and the Annual Report 2011 and 2015. Analysis of the data used in this research is multiple regression analysis using SPSS 16. Based on the results showed accept the hypothesis that the variable Profitability significant negative effect on Tax Avoidance and reject three other hypothesis. The results of this study demonstrate Corporate Social Responsibility and Executive Characteristics negative and not significant effect on Tax Avoidance and the Political Connections positive and significantly effect on Tax Avoidance. Variable control of the Audit Committee negative and significantly effect on Tax Avoidance. 35% Tax Avoidance variable explained by CSR, profitability, Executive Characteristics and Political Connections while the remaining 65% described other variables outside the model.